2023
DOI: 10.1002/jso.27294
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of oncoplastic surgery: Is there a learning curve?

Abstract: Introduction: Oncoplastic surgery (OPS) is a form of breast conservation surgery involving partial mastectomy followed by volume displacement or replacement surgery. As the field of OPS is growing, we sought to determine if there was a learning curve to this surgery.Methods: A retrospective chart review was conducted of all patients who underwent OPS over a 6-year period with a single surgeon formally trained in both Plastic Surgery and Breast Oncology. Cumulative summation analysis (CUSUM) was performed on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The frequency of the following factors increased with BMI, independent of the type of analysis: diabetes mellitus (nonobese (6.5%) vs. Class 1 (17.9%) vs. Class 2 (23.9%) vs. Class 3 (32.5%), p < 0.001); hypertension (32.2% vs. 51.9% vs. 60.0% vs. 65.4%, p < 0.001); protein malnutrition (albumin <3.5 g/dL, 3.6% vs. 4.4% vs. 5.8% vs. 10.6%, p < 0.001); creatinine (0.80 mg/dL vs. 0.83 mg/dL vs. 0.85 mg/dL vs. 0.89 mg/ dL, p < 0.001); and operative risk, as predicted by the preoperative American Society of Anesthesiologists (ASA) physical status classification score (2.16 vs. 2.36 vs. 2.50 vs. 2.77, p < 0.001). 14 Moreover, a greater operative time was found as BMI increased (86.7 min vs. 94.7 min vs. 100.6 min vs. 99.6 min, p < 0.001). On the other hand, the groups did not differ significantly in number of outpatient versus inpatient procedures, smoking status, metastatic cancer, steroid use, or hematocrit levels (Table 1).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The frequency of the following factors increased with BMI, independent of the type of analysis: diabetes mellitus (nonobese (6.5%) vs. Class 1 (17.9%) vs. Class 2 (23.9%) vs. Class 3 (32.5%), p < 0.001); hypertension (32.2% vs. 51.9% vs. 60.0% vs. 65.4%, p < 0.001); protein malnutrition (albumin <3.5 g/dL, 3.6% vs. 4.4% vs. 5.8% vs. 10.6%, p < 0.001); creatinine (0.80 mg/dL vs. 0.83 mg/dL vs. 0.85 mg/dL vs. 0.89 mg/ dL, p < 0.001); and operative risk, as predicted by the preoperative American Society of Anesthesiologists (ASA) physical status classification score (2.16 vs. 2.36 vs. 2.50 vs. 2.77, p < 0.001). 14 Moreover, a greater operative time was found as BMI increased (86.7 min vs. 94.7 min vs. 100.6 min vs. 99.6 min, p < 0.001). On the other hand, the groups did not differ significantly in number of outpatient versus inpatient procedures, smoking status, metastatic cancer, steroid use, or hematocrit levels (Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…[30][31][32] While operative times may increase with a higher BMI given that there may be more tissue to dissect and reconstruct, physician experience in oncoplastic surgery also plays an independent role in OR time efficiency, with an increased experience level leading to less operative time. 14 As such, the results of this study may help facilitate the allocation of high BMI cases being delegated to experienced oncoplastic surgeons to offset the general increase in associated higher BMI cases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whomever makes the commitment to provide OPS techniques, previous literature is promising in that there is a quick learning curve. A retrospective review of over 200 patients over six years demonstrated competency in performing OPS after 24 procedures and mastery after 74 procedures ( 35 ), speaking to the necessity of training both breast and plastic surgeons in the surgical techniques that offer the best oncologic and aesthetic outcomes for eligible patients.…”
Section: Discussionmentioning
confidence: 99%